(untitled) (Repertorio Científico, 2025)
The province of Cartago, Costa Rica, is a significant horticultural production area of potatoes and onions, has attractive tourist areas and protected areas such as the Irazú Volcano National Park, and has great water potential, including the Reventado River basin. It presents a series of threats to water resources and other environmental problems such as erosion, contamination by agrochemicals, vulnerability in the supply of drinking water and its near exposure to a volcanic eruption. The present study aims to zone the priority areas of the Reventado River basin necessary to organize the territory and rehabilitate the most vulnerable areas to improve land productivity, water resources and development of the communities in the study area. The methodological procedure used biophysical data such as soil erosion, slope, protection zones, land use and land use conflicts. The data were modeled and priority area maps were created using the weighted overlay method, which involves combining the layers of the selected factors according to their weight and priority. The basin registered moderate to low erosion, corresponding to 60.38% of the soil. Then, the area near the Irazú volcano, as well as the Sapper, Retes and Cabeza de Vaca hills, exhibits slopes exceeding 40%. It was detected that, in the middle and lower areas of the basin, numerous buffer zones of rivers and ravines are not maintained in good condition. The greatest use 27.73% of the land is manifested in forest cover. Class A occupies approximately 22.22 km2 in the basin, from the middle to the lower area, formed by areas with urban occupation and agricultural crops. It was determined that 46.50% of the area has an appropriate land use and it was established that the highest percentage of the area is of low priority (about 30.15%), distributed throughout the basin, and is concentrated mainly in the high area near the Prusia sector and in the middle and low areas.